Psychometric evaluation of the NTDT-PRO questionnaire for assessing symptoms in patients with non-transfusion-dependent beta-thalassaemia. Issue 3 (22nd March 2023) - Taher, Ali T; Musallam, Khaled M; Viprakasit, Vip; Kattamis, Antonis; Lord-Bessen, Jennifer; Yucel, Aylin; Guo, Shien; Pelligra, Christopher; Shields, Alan L; Shetty, Jeevan K; Miteva, Dimana; Bueno, Luciana Moro; et al.
Abstract : Objectives: The non-transfusion-dependent beta-thalassaemia-patient-reported outcome (NTDT-PRO) questionnaire was developed for assessing anaemia-related tiredness/weakness (T/W) and shortness of breath (SoB) among patients with NTDT. Psychometric properties were evaluated using blinded data from the BEYOND trial (NCT03342404 ). Design: Analysis of a phase 2, double-blind, randomised, placebo-controlled trial. Setting: USA, Greece, Italy, Lebanon, Thailand and the UK. Participants: Adults (≥18 years) (N=145) with NTDT who had not received a red blood cell transfusion within 8 weeks prior to randomisation, with mean baseline haemoglobin level ≤100 g/L. Measures: NTDT-PRO daily scores from baseline until week 24, and scores at select time points for the 36-Item Short Form Health Survey version 2 (SF-36v2), Functional Assessment of Chronic Illness Therapy–Fatigue (FACIT-F) and Patient Global Impression of Severity (PGI-S). Results: Cronbach's alpha at weeks 13–24 was 0.95 and 0.84 for the T/W and SoB domains, respectively, indicating acceptable internal consistency reliability. Among participants self-reporting no change in thalassaemia symptoms via the PGI-S between baseline and week 1, intraclass correlation coefficients were 0.94 and 0.92 for the T/W and SoB domains, respectively, indicating excellent test–retest reliability. In a known-groups validity analysis, least-squares mean T/W and SoB scores at weeks 13–24 were worse in participants with worse scores for the FACIT-F Fatigue Subscale (FS), SF-36v2 vitality or PGI-S. Indicating responsiveness, changes in T/W and SoB domain scores were moderately correlated with changes in haemoglobin levels, and strongly correlated with changes in SF-36v2 vitality, FACIT-F FS, select FACIT-F items and the PGI-S. Improvements in least-squares mean T/W and SoB scores were higher in participants with greater improvements in scores on other PROs measuring similar constructs. Conclusions: The NTDT-PRO demonstrated adequate psychometric properties to assess anaemia-related symptoms in adults with NTDT and can be used to evaluate treatment efficacy in clinical trials.